Modulation of the transport of valproic acid through the blood-brain barrier in rats by the Gastrodia elata extracts. (5th October 2021) - Yang, Ling; Lin, I-Hsin; Ting, Chin-Tsung; Tsai, Tung-Hu
Abstract: Headings ethnopharmacological relevance: Valproic acid (VPA) is primarily used as a medicine for the treatment of seizures. Gastrodia elata ( G. elata ) extract has been used as an alternative medicine for epilepsy patients. Cotreatment with VPA and G. elata extract is commonly prescribed in Taiwan and mainland China. Nevertheless, the mechanism of the blood-brain barrier (BBB) transportation effect of G. elata extract on VPA has not been characterized. Aim of study: Our hypothesis is that G. elata extract modulates the BBB penetration of VPA through specific transporter transfer. Materials and methods: A validated liquid chromatography-tandem mass spectrometry and multiple microdialysis method was developed to simultaneously monitor VPA in the blood and brain of rats. To investigate the mechanism of BBB modulation by the G. elata extract on VPA in the brain, cyclosporin A, a P-glycoprotein (P-gp) inhibitor and organic anion transporting polypeptide (OATP) inhibitor, was coadministered with the G. elata extract and VPA. Results: The pharmacokinetic results demonstrated that the VPA penetration ratio of the BBB, determined by the area under the concentration curve (AUC) ratio of VPA (AUCbrain /AUCblood ), was approximately 0.36. After treatment with the G. elata extract (1 and 3 g/kg, p.o. for 5 consecutive days), the VPA penetration ratios were significantly enhanced to 1.47 and 1.02, respectively. However, in the experimental group coadministered cyclosporin A, the G. elata extract was unable to enhance the BBB transportation of VPA. Instead, the VPA penetration ratio in the brain was suppressed back to 0.38. Conclusions: The present study reveals that the enhancement effect of the transporter mechanism of G. elata extract on VPA transport into the brain occurs through the OATP transporter but not the P-gp transporter. Graphical abstract: Image 1